Mixed-methods analysis of satisfaction during a 12-session mindfulness-based intervention for women with a substance use disorder and trauma symptomatology - Bautista, Tara G.; Ware, Orrin D.; Macias Burgos, Miracle A.; Rivas, Veronica D.; Cruz-Carrillo, Yesenia; Davidson, Alec; Mezhenska, Mariia; Sanchez, Mariana; Amaro, Hortensia (Frontiers in Psychology, 2024)
Satisfaction with an intervention influences the uptake of behavior changes and the long-term efficacy of the intervention. Therefore, it is crucial to assess satisfaction by participant profile when creating and adapting behavior interventions for minoritized populations. Qualitative and quantitative data on participant trauma symptom severity and intervention satisfaction were collected through self-report surveys from 54 women. The sample was 59.3% Hispanic, with an average age of 33.21 (SD = 10.42), who were in residential treatment for substance use disorders (SUDs) and participated in a 12-session mindfulness-based intervention. Qualitative responses were coded using thematic analysis, and an integrative mixed-methods approach was used to compare qualitative theme frequency between high-trauma (N = 28) and low-trauma (N = 26) groups at session 2 and session 11. High- and low-trauma groups were determined by interquartile ranges (bottom 25% = low; top 75% = high). In session 2, the low-trauma group reported significantly higher satisfaction (M = 4.20, SD = 0.55) than the high-trauma group (M = 3.77, SD = 0.89); t(43) = 1.90, p = 0.03. In session 11, there was no significant difference between groups. The mixed-methods analysis revealed that “trouble focusing” appeared more frequently in the high-trauma group than in the low-trauma group during session 2, but the theme was not present in either group at session 11, suggesting that this might pose an initial barrier for individuals with high trauma but subsides as the intervention progresses. This speaks to the importance of retention strategies tailored for participants with SUDs and high trauma while they adjust to the intervention. Assessing initial challenges with satisfaction may help facilitators intervene to increase participant satisfaction.